Hydrogen evolution and capacitance behavior of Au/Pd nanoparticle-decorated graphene heterostructures. (September 2017) - Toth, Peter S.; Velický, Matěj; Slater, Thomas J.A.; Worrall, Stephen D.; Haigh, Sarah J.
Graphical abstract: Highlights: Single-metal and bi-metal graphene heterostructures are prepared at liquid/liquid interfaces. The asymmetrically decorated graphene nanocomposites are characterized using high-resolution transmission electron microscopy and 3D electron tomography. The electrochemical performances of the graphene-based hybrid materials are investigated using micro-droplet setup. Abstract: The outstanding properties of two-dimensional materials such as graphene offer the possibility to produce novel hybrid materials with boosted functionality for use in catalysis and electrochemical energy storage. The hydrogen evolution reaction and interfacial capacitance performance of monolayer graphene sheets decorated with various metal nanoparticles are studied herein. Chemical vapor deposition grown graphene monolayer was decorated with Au and/or Pd nanoparticles, either on one side or both sides, forming single- or bi metal graphene heterostructures. These asymmetrically decorated graphene nanocomposites were characterized using high-resolution scanning transmission electron microscopy and 3D electron tomography. Electrochemical characterization reveals enhanced hydrogen evolution activity and outstanding capacitance for the resultant composite materials in comparison to pristine graphene and other recently developed graphene-based energy storage devices.